An Eight-Step Guide to Creating and Sustaining a Mentoring Program. Issue 1 (2nd January 2017) - Vance, Eric A.; Tanenbaum, Erin; Kaur, Amarjot; Otto, Mark C.; Morris, Richard
ABSTRACT: Mentoring is an extremely valuable activity for both individuals and organizations. Mentoring within organizations can develop and integrate employees into their corporate culture. Mentoring outside the mentees' work groups or through professional development organizations can give broader perspective and support, especially in times of transition. But mentoring programs require tremendous effort to start, organize, and maintain. Few last more than two years. This article provides a structured approach to starting and sustaining a successful program. The steps include understanding an organization's particular needs, learning from small pilot programs, following up with mentoring pairs during a committed formal mentoring period, and evaluating results from each program's cycle to learn and grow the program. Supplementary materials for this article are available online.